2022
DOI: 10.1049/ipr2.12528
|View full text |Cite
|
Sign up to set email alerts
|

Graph convolutional network‐based image matting algorithm for computer vision applications

Abstract: Image matting plays a vital role in a variety of computer vision tasks including video editing and image fusion. Previously presented image matting algorithms might fail in producing favorable results since most of them concentrate on the similarity between the neighboring pixels while neglecting the corresponding spatial relationship. To address this issue, an end-to-end image matting framework through leveraging deep learning mechanism and graph theory is proposed. The proposed pipeline is a concatenation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…The study's findings supported the model's predictions. The outcomes confirmed the model's accuracy in image processing, which is extremely beneficial in boosting the visual impression [7]. A transformer fault diagnosis model based on a graph convolutional network was created by W. Liao.…”
Section: Introductionmentioning
confidence: 59%
See 2 more Smart Citations
“…The study's findings supported the model's predictions. The outcomes confirmed the model's accuracy in image processing, which is extremely beneficial in boosting the visual impression [7]. A transformer fault diagnosis model based on a graph convolutional network was created by W. Liao.…”
Section: Introductionmentioning
confidence: 59%
“…According to the uniform division strategy, a consistent weight vector 1 w exists for each node and neighbouring point of the face expression key point, at which point the graph convolution is implemented as shown in equation (7).…”
Section: Stitjmentioning
confidence: 99%
See 1 more Smart Citation
“…Li et al found that previously presented image matting algorithms might fail to produce favorable results since most of them concentrate on the similarity between the neighboring pixels while neglecting the corresponding spatial relationship. To address this issue, an end-to-end image matting framework through leveraging deep learning mechanism and graph theory is proposed [5]. Wang analyzed the development of traditional hand-woven craftsmanship into modern three-dimensional works, which had a positive impact on people's lives, for example, the application of fber art in specifc products [6].…”
Section: Related Workmentioning
confidence: 99%
“…Graph convolutional networks can be utilized to learn representations of nodes and edges in a graph, and can be used for tasks such as node classification, link prediction and graph classification. Graph convolutional networks have been utilized in a variety of applications including drug discovery, recommendation systems and natural language processing [8] .…”
Section: Introductionmentioning
confidence: 99%